DNA–schottky diodes for detection of alpha particles / Hassan Maktuff Jaber al-Ta’ii - Hassan Maktuff , Jaber al-Ta’ii (2016)
Physical properties of materials are significantly influenced by radiation, especially alpha radiation. When an energetic electron beam penetrates through a biomaterial such as deoxyribonucleic acid (DNA), various modifications occur according to the characteristics of the type of radiation involved. DNA, the blueprint of life, has in recent times been shown to feature exciting semiconducting behavior. It has opened-up great prospects in utilizing these DNA diodes in nanotechnology and nanoelectronics. Therefore, DNA electronics could allow for more sensitive, accurate and effective sensors to be developed and fabricated. The aims of this study were to develop a metal-semiconductor or Schottky diode and measure its electrical characteristics or diode parameters such as ideality factor, series resistance and barrier height under both the presence and absence of alpha radiation. These parameters were measured using conventional current-voltage (I–V) method, Cheung and Cheung’s functions and modified Norde’s function. The present work was conducted in three stages. The first involves utilizing DNA as a semiconducting material in three different metal-DNA-metal (MDM) structures. Aluminium (Al) thin film evaporated using thermal evaporation technique was used for fabricating the MDM structures; Al/DNA/Silicon (Si)/Al, Al/DNA/Indium tin oxide (ITO) and DNA/Al. Its electrical behaviors before and after exposure to alpha irradiation (up to 40 min or 0.24 Gy) were studied through its (I–V) response curves. Acquisition of the I–V curves demonstrated that the DNA based MDM diodes exhibited clear rectifying behavior. This was followed by the second stage, which involved real-time detection of alpha particle by means of the I–V–time profile using the Al/DNA/Al structure with 30 μm gap between the electrodes. We obtained the Φ barrier height value calculated by using the conventional method for non-radiated structure at about 0.715 eV, increasing to 0.737 eV after 4 min of radiation. Barrier height values were observed to increase after 20, 30 and 40 min of radiation, except for 6, 8 and 10 min, which registered a decrease of about 0.67 eV. This was in comparison with the Cheung and Cheung’s method, which registered 0.6983 eV for non-radiated increasing to 0.7528 after 2 min of irradiation. The barrier height values meanwhile were observed to decrease after 4 min (0.61 eV) to 40 min (0.6945 eV). The study shows that conventional thermionic emission model could be practically utilized for estimating the diode parameters including the effect of series resistance. These changes in the electronic properties of the Al/DNA/Al junctions could therefore be utilized in the manufacture of sensitive alpha particle sensors. Finally, the last stage of this work involves utilizing the Al/DNA/Al structure as a humidity sensor based on the environmental conditions exposed to low and high doses of radiation under varying percentage relative humidity (%RH). We also examined the effect of different humidity conditions on the capacitive and resistive response of the Al/DNA/Al Schottky barrier structures when bombarded by time-dependent dosages of alpha particles. Results for the low doses observed generally pointed towards a decrease in the resistance value from the pristine to the radiated structures. A high of 1678 to a low of 6.523 KΩ and 1512 to 1.801 KΩ were observed for the non-radiated and 2 min of alpha irradiation, respectively. It was also demonstrated that under the effect of humidity, the capacitance of the DNA thin film increased from 0.05894 to 92.736 nF, with rising RH levels. These observations may suggest the exciting possibility of utilizing Al/DNA/Al Schottky barrier diodes as potentially sensitive humidity sensors.